Antagonistic activity of extracts of Edible mushroom pleurotus osreatus Against some fungi isolated from soil - Asal Faiz Hameed Aldabbgh; Abdalkarim S.Hasan Alnuaimi (Tikrit Journal of Pure Science, 2021)
The results of the current study that the extract of the food fungus Pleurotus sp and its compounds isolated from it have an effect in inhibiting the growth of some fungi isolated from the soil. Thus, different concentrations were used and in three ways are: the method of high concentration, wells method and disc method. where the aqueous extract using the high concentrations method showed better results than the ethanolic extract against some isolated fungi under study, especially at the concentration (2.5) (2) (1.5) ml except for Penicillium natatum, which gave a slight growth at two concentrations of (2.5) (2) ml. As for the tablets method, where the ethanolic extract had a greater effect on the growth of the fungi under study than the aqueous extract, and the results of the wells method for the extract showed. The aqueous extract edible mushroom pleurotus sp. More effective than ethanolic extract.